The Association Between Preterm Premature Rupture of Membranes and Surgical Site Infection Following Cesarean Section - Mehmet Çınar; Hakan Timur; Ali İrfan Güzel; Aytekin Tokmak; Burak Ersak; Sibel Saygan; Dilek Uygur (Medical Network, 2016)
OBJECTIVE: To evaluate clinical characteristics of surgical-site infections (SSIs) following cesarean section (CS) and to identify infection rates and risk factors associated with SSIs following cesarean section. STUDY DESIGN: A total of 197 patients who underwent cesarean and complicated with SSIs was evaluated during hospital stay or within 30 days following cesarean section by readmission to the hospital or by post discharge survey. The clinical characteristics, subsequent microbiological culture results and management were recorded. RESULTS: There were 34 (17.25%) patients complicated with preeclampsia and 26 (13.17%) gestational diabetes mellitus (GDM) in the study group. Preterm rupture of membranes (PROM) rate was 17.31% and mean rupture period were 6.61 hours. In the study population, 66 patients had positive culture results. The most isolated microorganism was S. Aureus (n=13, 19.7%). Preeclampsia, GDM and PROM rates were statically significant high in patients with positive culture results (p<0.05). There were 31 patients complicated with PROM in the study group. The rates of positive culture results were significantly increased by PROM (mean 45%, p<0.05). CONCLUSION:  Independent risk factors for post-cesarean SSIs are younger age, obesity, diabetes, hypertension, premature rupture of membranes. Information regarding higher rates of SSIs should be provided to obese women undergoing cesarean delivery, especially when diabetes and hypertension coexists.